Preparedness of the teachers for Team-Based Learning: Liking, disliking and suggestions of faculty - Abdus Salam,Siti Mariam Bujang,Mohammad Arif Kamarudin,Mohamad Nurman Yaman,Harlina Halizah Siraj,Nabishah Mohamad (Journal of Applied Pharmaceutical Science, 2016)
Faculty development is an integral part of institutional development. This paper describes liking, disliking and suggestions of faculty members on a 2-days Team-Based Learning faculty training workshop, where 39 faculty members were attended. Participants liked the lively and informal discussions through which they got a new technique to teach students more interactively. However, they disliked too short demonstration and short notification given them to read pre-assigned material and suggested more workshops with more practical demonstration before its implementation. Faculty developers should address the needs of the faculty while organizing developmental workshop aimed to link between theory and practice for a sustainable development.
Keywords: Team based learning,preparedness workshop,perspectives of Faculty.